Hubungan Demensia dengan Tingkat Ketergantungan Pemenuhan ADL (Activity of Daily Living) pada Lansia di Panti - Citra Windani Mambang Sari; Fitri Fatimah Zakiati; Indra Maulana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Dementia is a collection of symptoms that occurs progressively with cognitive decline marked by change in behavior, decreased memory or remembrance, orientation, difficulty in communication and making decisions that will affect normal social and occupational activities. The decline that will occur in the elderly can cause problems such as long-term memory and information processing, the elderly will have difficulty in re-expressing incidents or events experienced. This research aimed to determine whether there is a relationship between dementia status and the dependency level of elderly in fulfillment of ADL (activity of daily living) at Tresna Werdha Social Home. The type of this research was descriptive correlational with cross sectional approach, the total sampling technique with a sample of 60 elderly in PSTW. The research instrument used a 3MS questionnaire (Modified Mini Mental State Test) and Barthel Indeks. Univariate analysis used frequency and percentage and bivariate analysis used the Chi Square test. In this research, the result obtained that respondents experienced moderate dementia with a percentage (53.3%) and most of the ADL needs of partial dependence elderly with a percentage (46.7%). There was a significant relationship between dementia and the dependency level of elderly in fulfillment of ADL (activity of daily living) at PSTW with sig. (significant) = 0.000 (P Value≤0.05). With this relationship can create better nursing services for the elderly so as not to experience a decline in cognitive function early and be able to meet their ADL needs.